2023
DOI: 10.56397/jrssh.2023.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Complementary Feeding Practices on Nutritional Status of Children Between 6 to 24 Months in Kisumu County, Kenya

Abstract: Despite complementary feeding practices among mothers with children aged 6 – 24 months, death and disease infection rates are still escalating regardless of the nutritional status of children within that age gap. Complementary feeding practices plays a key role in providing the much-needed nutrients as it enhances successive development and general wellbeing of children, 6-24 months. A few research studies have been conducted in Kisumu County, more specifically, Kisumu County Referral Hospital on complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…This contrasts with the findings of previous studies conducted in Unaizah, Saudi Arabia, and Cross River State, Nigeria, which reported a lack of knowledge among mothers regarding complementary feeding [14,15]. However, it aligns with several other studies indicating that the majority of participants demonstrated a high level of knowledge regarding complementary feeding [16][17][18]. Furthermore, this study's results closely resemble those of a study conducted in Jazan, which revealed that 49% of the participants achieved a high knowledge score [19].…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with the findings of previous studies conducted in Unaizah, Saudi Arabia, and Cross River State, Nigeria, which reported a lack of knowledge among mothers regarding complementary feeding [14,15]. However, it aligns with several other studies indicating that the majority of participants demonstrated a high level of knowledge regarding complementary feeding [16][17][18]. Furthermore, this study's results closely resemble those of a study conducted in Jazan, which revealed that 49% of the participants achieved a high knowledge score [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Human rights organizations have worked to raise awareness of the impact of such practices on widows and the psychological impact is evident in research. Akinyi (2023) reported a correlation between widowhood and poor psychological health and Muthangya (2019) reported depressive symptoms among widows in Kenya. Further, Wilcox et al ( 2003) report negative effects on mental health and mental health outcomes.…”
Section: Navigating Widowhood Within Cultural Expectationsmentioning
confidence: 99%